2018
DOI: 10.1080/21645515.2018.1543522
|View full text |Cite
|
Sign up to set email alerts
|

Cost-impact study of rotavirus vaccination programme in Scotland

Abstract: Aim: In July 2013, the Scottish Government introduced a rotavirus vaccination programme into the childhood immunisation schedule. The aim of this research was to estimate the cost-impact of this programme. Methods: Data for rotavirus-related resource use were identified including laboratory reports, hospitalisations, attendances at accident and emergency departments (A&E), general practice consultations (GP), calls to the National Health Service telephone helpline (NHS24) and prescriptions for common rehydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Despite the progress, enrolment of rotavirus immunization in national immunization programs remains incomplete in Europe. 31,41 Heggie and colleagues describe the cost-impact of rotavirus immunization in Scotland 42 following the introduction of universal rotavirus immunization in 2013. In Latvia such a program was introduced only in 2015, a decision that was strengthened by the substantial disease burden of rotavirus gastroenteritis in Latvia, as demonstrated in this issue by Tafalla et al 43 The success of rotavirus vaccines in reducing the burden of diarrheal diseases opens new era toward the prevention of diarrheal diseases caused by other enteric viruses, such as norovirus.…”
Section: Rotavirus Vaccinesmentioning
confidence: 99%
“…Despite the progress, enrolment of rotavirus immunization in national immunization programs remains incomplete in Europe. 31,41 Heggie and colleagues describe the cost-impact of rotavirus immunization in Scotland 42 following the introduction of universal rotavirus immunization in 2013. In Latvia such a program was introduced only in 2015, a decision that was strengthened by the substantial disease burden of rotavirus gastroenteritis in Latvia, as demonstrated in this issue by Tafalla et al 43 The success of rotavirus vaccines in reducing the burden of diarrheal diseases opens new era toward the prevention of diarrheal diseases caused by other enteric viruses, such as norovirus.…”
Section: Rotavirus Vaccinesmentioning
confidence: 99%
“…Studies from the UK, Spain, and Italy, show that a universal vaccination against rotavirus has significant clinical and economic benefits [ 12 14 ]. A study investigating the drivers of vaccination uptake in Naples (Italy) in 2018 among parents of children aged between 3 months and 3 years showed that only 15.3% reported having vaccinated their children against rotavirus infection, but that over half of the respondents would be willing to have the vaccine [ 15 ], a figure very close to the one from national coverage data for 2018 published by the Italian Ministry of Health (MoH) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of rotavirus vaccines has led to a significant reduction in diagnosed infections, visits to emergency departments and hospital admissions due to rotavirus [7,[16][17][18]. Furthermore, rotavirus vaccinations have been shown to be cost-effective in high-income countries, and may even be cost-saving [19][20][21][22]. Financial benefits may vary between countries due to differences in cost of care [19,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rotavirus vaccinations have been shown to be cost-effective in high-income countries, and may even be cost-saving [19][20][21][22]. Financial benefits may vary between countries due to differences in cost of care [19,23,24]. Neither epidemiological studies, estimates of disease burden, nor cost-effectiveness calculations of rotavirus vaccination have previously been done in Iceland.…”
Section: Introductionmentioning
confidence: 99%